A STUDY OF CODE SWITCHING USED BY THE PRESENTER IN X- FACTOR INDONESIA 2013 PROGRAM ON RCTI - KURNIAWATI, SINTA DWI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Code, Code Switching, X-Factor.People use language to communicate each other. In communication, when two or many people communicate to each other by using different language, the communication will not be understood. Generally, people who lived in bilingual or multilingual environment use code switching to prevent a misunderstanding between them because of the differences of language used. This research is aimed to find out code switching used by the presenter of “X-Factor Indonesia”. Besides, this research is also to identify the kinds of code switching used by the presenter of “X-Factor Indonesia”. As a result, the writer conducted a research which is aimed to find out: (1) What kinds of code switching are used by the presenter of “X-Factor” in RCTI, and (2) What are the factors facilitating the presenter of “XFactor” to use code switching. The writer used the theory of Romaine (1995) and Holmes (2001).The writer used descriptive or qualitative approach as the research method, while the subject of this research is the presenter of “X-Factor”. The writer collected 100 data containing code switching. This research used code switching theory of Romaine (1995) because this theory has suitable and clear explanation about kinds of code switching. To answer the second question, the writer used the theory of Holmes (2001). Based on Holmes' (2001) theory, there are four factors affected people used code switching.The result of this research showed that the most type of code switching in the utterances done by the presenter of “X-Factor Indonesia” is intra-sentential. This type occurred 88 times (88%). The second type is inter-sentential which occurred 8 times (8%), and the last type is tag switching which occurred 4 times (4%). While, the factors affecting the code switching is participants which occurred 17 times (17%), solidarity which occurred 68 times (68%), status which occurred 9 times (9%), and the last is topic which occurred 6 times (6%).Finally, the writer suggests the future researchers who will do the same research understand more about code switching. Besides, they should also analyze the factors affecting people in using code switching. The writer suggests them use the latest theory of code switching. This result of the research can be used for the next researchers as their reference in doing the next research in other phenomena of code switching occurred in television.